ANALYSIS OF YOUNG ADULT’S INTENTION TO USE INDONESIAN PREPAID ELECTRONIC MONEY - Immanuel, Edgar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2021)
Electronic money is one of the non-cash payment instruments that has grown rapidly in the last decade and is considered to be boosting the economy in Indonesia. There are 37 products of electronic money that have been registered under Bank Indonesia. The main focus of this research is to analyze young adultâ€™s intention to use electronic money. This study examines three main factors that influence the intention to use electronic money namely attitude, subjective norms, and perceived behavioral control. The results indicate that attitudes, subjective norms, and perceived behavioral control have significant influence on the intention to use electronic money. In addition, the variable with most significant influence is perceived behavioral control, while subjective norms are the lowest. Therefore, to increase the use of electronic money and promote a cashless society, the most suitable step for the government and companies is to increase the ease of access to electronic money. The easier and more practical the use of electronic money, the more people will use it and even reach users from elderly and underage age groups.Â Keyword: electronic money, theory of planned behaviour, intention to use e-money